Are children with obesity at school entry more likely to have a diagnosis of a musculoskeletal condition? Findings from a systematic review - Carol Dezateux; Nicola Firman; Gill Harper; Marta Wilk (BMJ Publishing Group, 2022)
Background Children with obesity at school entry are at increased risk of persistent obesity throughout childhood and adulthood. Little is known about associations with adverse health outcomes with onset during childhood including those affecting the musculoskeletal system. We examined the association between obesity present at school entry and adverse musculoskeletal diagnoses with onset during childhood.Methods We searched three electronic databases to identify longitudinal studies published in English between January 2000 and June 2022 assessing associations between obesity measured at school entry (around age 5 years) and musculoskeletal diagnoses made before age 20 years. Two reviewers screened titles, abstracts and full-text using EPPI-Reviewer software. Bias and quality of eligible studies were appraised using The Quality Assessment tool for Observational Cohort and Cross-sectional studies and findings synthesised.Results We identified four eligible studies from 291 unique records, three conducted in Spain and one in Scotland. These studies reported on 1 232 895 children (available data: 51.4% boys; none reported ethnic distribution) with study sample sizes ranging from <2000 to 600 000 and length of follow-up from 2 to 13 years. Quantitative synthesis of findings across these four studies was not possible due to differences in outcomes and effect sizes reported. Children with obesity at school entry were more likely to receive diagnoses of slipped capital femoral epiphysis, back pain, fractures and musculoskeletal complaints made in primary care settings. Included studies were assessed as of 'fair' to 'good' quality.Conclusion There is good to fair evidence to suggest children with obesity at school entry are more likely to receive a diagnosis of a musculoskeletal condition during childhood. Further research is needed to replicate these findings in ethnically diverse populations and to investigate whether these are causal associations. The implications of this for children's mobility and quality of life and future musculoskeletal health warrants further assessment.